Launch of a Nigerian agricultural policy researchers network - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
One of the key activities of the Agricultural Policy Support Facility (APSF) is to improve communication linkages and consultations between policymakers, policy analysts, and policy beneficiaries on agricultural and rural development policy issues. In the light of this, the APSF in October 2008 began to identify those who could contribute to evidence-based agricultural and rural development policymaking in Nigeria. This culminated in the development of a central database. The need to move from a database of agricultural policy researchers experts to a functional network of agricultural policy experts led to the launch of an Agricultural Policy Researchers Network. The launch brought together about twenty-nine participants from academia, research institutes, the Central Bank of Nigeria, the private sector, and the Ministry of Environment, among others. (See Appendix A for the participant list). The objective of the launch was to begin the process of formalizing exchange of knowledge and information among agricultural policy researchers. The forum deliberated on the appropriate vision, mission and goals for the network; how to ensure its sustainability; and other essential elements needed to kick start the activities of this network of professional agricultural policy researchers. (See Appendix B for the agenda.) The ultimate aim of this initiative is to establish a platform where researchers can network seamlessly from the comfort of their offices and ultimately have an active voice in the policymaking process in the country. The remainder of this report presents opening remarks, presentations, and discussions at the plenary, and next steps.